Geographies of Imaginaries and Environmental Governance. Issue 2 (4th March 2023) - Chhetri, Netra; Ghimire, Rajiv; Eisenhauer, David C.
Abstract : Storied to fit into the sociocultural practices and the materiality of a place, the geography of imaginaries has expanded within the disciplinary lexicon since the beginning of the twenty-first century. This Focus section advances both theoretical and empirical approaches that demonstrate how cultural, technological, and environmental imaginaries emerge, coalesce, and circulate among policy actors and others involved in the governance of the environment. It aims to fill an existing gap between more general studies of imaginaries in science, technology, and innovation and applied approaches that deal with particular outcomes in the governance of the environment. The articles within this Focus section contribute three key insights to our understanding of the complex relationships between imagination and environmental governance. First, the articles demonstrate that there are always multiple imaginaries at play when it comes to the governance of the environment. Second, and relatedly, they also examine how global-spanning imaginaries related to climate change, biodiversity, food security, and urbanization get translated into local cultural contexts. Finally, the articles demonstrate that effective environmental governance requires imagination while also showing that imagination is not a panacea. Imagination, however, opens up possibilities for rethinking human–environment relationships for envisioning radically different futures.